Low-grade sarcoma of the cervix: an unusual diagnosis - Maurice José González Basulto; Gustavo de Jesús Crespo Campo; Dayan Cervantes Peláez (Acta Médica del Centro)
Introduction: Low-grade endometrial stromal sarcoma is a tumor that represents less than one percent of all uterine malignancies. It is mostly diagnosed between 40 and 55 years of age, it has slow growth, with extrauterine dissemination in 40 and up to 50% of cases at the time of diagnosis. Patient information: 72-year-old woman, with a history of high blood pressure, type 2 diabetes mellitus and surgery for fibroid, along with necrobiosis, who had to undergo total abdominal hysterectomy with double adnexectomy. As a result of the biopsy, submucosal and subserosal intramural leiomyomas with areas of necrosis and hemorrhages were detected. Subsequently, in August 2022, she presented scant bleeding, so she was sent to the Neck Pathology Consultation. She underwent video colposcopy with an exophytic lesion in the vaginal vault. The patient returned to the center due to a tumor measuring ±6 to 8 cm, violaceous, protruding through the vulvar introitus, coming from the vaginal vault and accompanied by bleeding, and friable. The biopsy result determined a low-grade sarcoma-type malignant mesenchymal tumor with two foci of necrosis. Conclusions: Uterine cancer is the most common gynecological malignancy. On the other hand, low-grade endometrial stromal sarcoma is a very unusual tumor that ranks second among uterine mesenchymal tumors.